A microspectroscopic insight into the resistivity switching of individual Ag-TCNQ nanocrystals - Rösner, Benedikt; Ran, Ke; Butz, Benjamin; Schmidt, Ute; Spiecker, Erdmann; Fink, Rainer (Physical Chemistry Chemical Physics, 2015)
We investigate the resistivity switching in individual Ag-TCNQ wires with on/off-ratios of up to 103. Raman and soft X-ray absorption microspectroscopy studies disclose reverse charge transfer. Quantifying of the fraction of neutral TCNQ within the switched material yields values up to 22.3%. These findings expedite the understanding of the switching process in Ag-TCNQ nanowires.

Switching behaviour of individual Ag-TCNQ nanowires: an in situ transmission electron microscopy study - Ran, Ke; Rösner, Benedikt; Butz, Benjamin; Fink, Rainer; Spiecker, Erdmann (Nanotechnology, 2016)
The organic semiconductor silver-tetracyanoquinodimethane (Ag-TCNQ) exhibits electrical switching and memory characteristics. Employing a scanning tunnelling microscopy setup inside a transmission electron microscope, the switching behaviour of individual Ag-TCNQ nanowires (NWs) is investigated in detail. For a large number of NWs, the switching between a high (OFF) and a low (ON) resistance state was successfully stimulated by negative bias sweeps. Fitting the experimental I-V curves with a Schottky emission function makes the switching features prominent and thus enables a direct evaluation of the switching process. A memory cycle including writing, reading and erasing features is demonstrated at an individual NW. Moreover, electronic failure mechanisms due to Joule heating are discussed. These findings have a significant impact on our understanding of the switching behaviour of Ag-TCNQ.
Keywords: Ag-TCNQ nanowires; in situ transmission electron microscopy; electrical switching; organic memory device; organic electronics